Establishment of uranium mining and processing operations in the context of sustainable development. - Ganguly, C.; Waggitt, P. (International Atomic Energy Agency, 2009)
Australia; Northern Saskatchewan, Canada; Alligators River; Alaska; Niger; Russian Federation; USSR; Germany; Hungary.
"STI/PUB/1401"--PDF t.p. verso.
"The IAEA officers responsible for this report were C. Ganguly and P. Waggitt of the Division of Nuclear Fuel Cycle and Waste Management"--PDF Foreword page.
Keywords: Uranium mines and mining -- Environmental aspects.; Uranium mines and mining -- Costs.; Sustainability.; elektronické knihy; electronic books